Analyzing Generation Z's Preferences and Behavior Patterns Toward Stationery Products: A Case Study of Shop B in Kabanjahe, North Sumatra - Krisanti, Jessica; Garnida, Nita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study examines Generation Z consumers' preferences and behavior patterns regarding stationery products, explicitly focusing on Shop B in Kabanjahe, North Sumatra. This research uses a quantitative research methodology to analyze the factors influencing purchase intentions among Generation Z consumers. Using a structured questionnaire and employing statistical techniques such as multiple linear regression, this research aims to provide insights into how preferences, behavioral control, the self-assurance regarding their ability to perform a particular behavior or action impact the purchasing decisions of this demographic. The findings will contribute to developing targeted marketing strategies to enhance customer engagement and loyalty.